MAKNA KATA MAKAN DAN KAKERU SEBAGAI POLISEMI (KAJIAN LINGUISTIK KOGNITIF) - nita rustanti (TEXTURA, 2018)
The purpose of this research is to describe polisemy of “makan” in Indonesian language and kakeru (掛ける) in Japanese language with cognitive linguistics perspective. “Makan” and kakeru (掛ける) has multiple meanings in Indonesian and Japanese languange and it became an obstacle for language leaners. This research used descriptive method. The result of this research showed that polisemy of “makan” in Indonesian language and kakeru (掛ける) in Japanese language evolve into metaphor, metonymy, and synecdoche.